Achieving Sustainable Development Goals from a Water Perspective - Bhaduri, Anik; Bogardi, Janos; Siddiqi, Afreen; Voigt, Holm; Vörösmarty, Charles; Pahl-Wostl, Claudia; Bunn, Stuart E.; Shrivastava, Paul; Lawford, Richard; Foster, Stephen; Kremer, Hartwig; Renaud, Fabrice G.; et al. (Frontiers in Environmental Science, 2016)
Efforts to meet human water needs at local scales may cause negative environmental externalities and stress on the water system at regional and global scales. Hence, assessing Sustainable Development Goals (SDGs) targets requires a broad and in-depth knowledge of the global to local dynamics of water availability and use. Furthermore, interactions and trade-offs between different SDG targets may lead to sub-optimal or even adverse outcomes if the set of actions are not properly pre-designed to consider such inter-linkages. Thus, scientific research and evidence have an important role to play in facilitating the implementation of SDGs through assessments and policy engagement from global to local scales. This paper addresses some of these challenges related to implementation and monitoring of the targets of the SDGs from a water perspective, based on the key findings of a conference organized in 2015 focused on three essential aspects of SDGs: indicators, inter-linkages, and implementation. The paper argues that indicators should not be too simple and should ultimately deliver sustainability measures. The paper highlights that remote sensing and earth observation technologies can play a key role in supporting the monitoring of water targets. It also recognizes that implementing SDGs is a societal process of development, and there is a need to link how SDGs relate to public benefits and to communicate this to the broader public.